A comparative study between local application of 10% zinc oxide to a combination of 10% zinc oxide and tocopherol in treating infant’s diaper dermatitis - Mirle, Nikhita; Rajan, Aswathy; Soans, Santosh T (Indonesian Pediatric Society, 2024)
Background Tocopherol is known to have an anti-inflammatory effect, thereby reducing erythema, edema, and skin irritation, which are the main pathologies observed in diaper dermatitis. Objective To compare the effect of local application of a combination of 10% zinc oxide and tocopherol in the treatment of infant diaper dermatitis with plain 10% zinc oxide. Methods A single-centric, prospective interventional study was conducted in a tertiary care hospital for 18 months where all children aged <1 year newly diagnosed with diaper dermatitis were selected. They were divided into two groups; one group received only 10% zinc oxide, while the other group received a combination of 10% zinc oxide and tocopherol for local application. Patients were assessed for rash dimensions, severity score of diaper dermatitis, and pH of the rash prior to starting treatment and at the end of 5 days. Statistical analysis was done using students paired two-tailed T-test. Results Out of 115 infants with diaper dermatitis, 88 were included in our study. The decrease in rash dimensions was greater in the study group (P=0.004). A mean diaper dermatitis severity score of 1.96±0.76 cm in the study group was noted on day five of the assessment (P<0.001). Conclusion The healing process in diaper dermatitis is accelerated when a combination of 10% zinc oxide and tocopherol is used. This study supports the evidence of expediting healing by tocopherol, which can be considered in treatment recommendations for diaper dermatitis.